Germline PARN Variants in Telomere Biology Disorders and Challenges in Variant Curation - Hasset T. Nurelegne; Mone't B. Thompson; Kelvin C. deAndrade; Ashley S. Thompson; Lisa J. McReynolds; Marena R. Niewisch; Sharon A. Savage (Molecular Genetics & Genomic Medicine, 2025)
ABSTRACT Background PARN encodes poly(A)‐specific ribonuclease, a 3 exoribonuclease important in regulating RNA stability and maturation. Rare germline PARN variants have been reported in telomere biology disorders (TBDs) leading to its inclusion on gene panels for bone marrow failure syndromes and pulmonary diseases. Methods To understand the extent of germline PARN variation in human disease, we conducted a comprehensive literature review, curated the TBD‐associated PARN variants using AutoGVP and in silico prediction tools (MetaSVM, REVEL, and/or CADD) and assessed their frequency in the gnomAD database. Results Ninety‐three unique PARN variants were identified in the literature as present in individuals or families affected by TBDs, but clinical features were not consistently reported. Forty‐one variants (44.1%) were classified as pathogenic or likely pathogenic. These variants were spread across the entire gene with no obvious clustering. gnomAD data were notable for a paucity of common variants and metrics suggesting PARN variation would be tolerated. Conclusion The extent to which specific PARN variants can be associated with TBD etiology is limited due to incomplete literature, clinical data, lack of robust functional assays, and high frequency of rare variants.